RANCANGAN HUMAN RESOURCES ANALYTICS UNTUK PELATIHAN KARYAWAN PEMASARAN PENJUALAN DI RESTORAN X - Triningtyas Elisabeth Putri Gusti; Theresia Gunawan; Agus Gunawan (Jurnal Administrasi Bisnis, 2022)
The increasing number of restaurants leads to competition in service, the restaurant will provide perfect service to keep consumers visiting again. The quality of reliable human resources in service, especially in the marketing and sales divisions, is the best way said restaurant owners according to restaurant representatives. Training and development will create quality human resources that adapt to service developments. These services are business-to-business and business-to-consumer which have different consumer characteristics. The research purpose is to examine human resource analytics information systems in determining prospective employees’ training with limited funds.. Interviews and focus group discussions were conducted in this study. A qualitative approach using the business challenge bundle method and business process model and notation is used to analyze the data. Data was collected from interviews and focus group discussion.There are five stages of the module. The first module is about the skill map, the second is the training map, the third is the performance map, the fourth is about the behavior map, and the fifth is the design of the Human Resource Analytics system which has been integrated from modules 1 to 4.